WAKAF PRODUKTIF - Khusaeri Khusaeri (UIN Raden Mas Said Surakarta, 2015)
Historically, the development of Muslim community,especially in Indonesia, has indicated that wakaf has a big contribution.As big as its role, people may not be able to think about how Muslimcommunity could develop without without wakaf. Nevertheless, thosedevelopments also bring various critics, especially regarding on thephenomena of comsumtif wakaf in the sosciety. There were limitedwakaf which were cultivated productively, in which the benefit could beused to be able to support the poor people. As its consequences, therewere some cases that showed that wakaf was not able to coverpeople/society needs. Therefore, the exact and proper metode incultivating wakalf nowadays is really needed.